Fully subthreshold current-based characterization of interface traps and surface potential in III-V-on-insulator MOSFETs - Kim, Seong Kwang; Lee, Jungmin; Geum, Dae-Myeong; Park, Min-Su; Choi, Won Jun; Choi, Sung-Jin; Kim, Dae Hwan; Kim, Sanghyeon; Kim, Dong Myong (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
We report characterization of the interface trap distribution (D-it(E)) over the bandgap in III-V metal-oxide- semiconductor field-effect transistors (MOSFETs) on insulator. Based only on the experimental subthreshold current data and differential coupling factor, we simultaneously obtained D-it(E) and a nonlinear mapping of the gate bias (V-GS) to the trap level (E-t) via the effective surface potential (psi(S),(eff)). The proposed technique allows direct extraction of the interface traps at the In0.53Ga0.47As-on insulator (-OI) MOSFETs only from the experimental subthreshold current data. Applying the technique to the In0.53Ga0.47As channel III-V-OI MOSFETs with the gate width/length W/L = 100/50, 100/25, and 100/10 mu m/mu m, we obtained D-it(E) congruent to 10(11)-10(12) eV(-1) cm(-2) over the bandgap without the dimension dependence. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: OXIDE INTERFACE; STATES